Exploring the influence of demographic factors on COVID-19 prevention behaviors in traditional market settings - Aliyah, Nurul; Purba, Imelda Gernauli (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Covid-19 prevention behaviors are essential in controlling the spread of the virus, particularly in public spaces such as traditional markets. This study aimed to analyze the factors influencing the Covid-19 prevention behavior of traders at Yada Traditional Market, Palembang. Previous studies have indicated that demographic factors such as age, gender, education level, and knowledge significantly impact preventive actions. Methods: his cross-sectional study involved 110 traders as respondents, utilizing a structured questionnaire for data collection. Descriptive and inferential statistics, including Chi-Square and logistic regression, were employed to analyze the relationships between demographic factors and Covid-19 prevention behavior. Findings: The study found no significant relationship between gender and Covid-19 prevention behavior (p-value=0.156). However, significant associations were found between age, education level, and knowledge with prevention behavior (p-value<0.05). Older adults and individuals with higher education levels exhibited better prevention behaviors. Conclusion: Age, education, and knowledge were identified as key factors influencing Covid-19 prevention behaviors. This suggests that improving education and knowledge could enhance preventive measures among traders and the broader community. Novelty/Originality of this article: This study provides new insights into the Covid-19 prevention behavior of traders in a traditional market setting, highlighting the importance of demographic factors in health behavior interventions.